(3cJH GdfHi Udi Gddg Ydjg hSde hcJH CNQis ((3eOQSI TeS HGTG HeOjfI GScOGQNhT OGQ s)
(3ChdgG (B:s
(3gPG cJGH JHg eMeO Hf YHO Gddg Edi cGaI GdfGS CLeYjf QShdg HTjQkG hfPjQkG heDJefkG Ydi hOjYI Gddg ai Ndbg s
(3BNQgG (B:s
(3ef GdebhbS Edi GdfHi Udi Gddg Ydjg hSde bhdg (B: (3deMeO Hf YHO Gddg ef GdebhbS YXje GdbHW CeG HYO abO bQCJ cJGHc hGdSdGe Ydi ef GJHY GdgOi s
(3cJH YfhGfGJ GdcJH hHYV GdMhGTi HGdaGQSjIs
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJGQjNs